Effects of Buchholzia coriacea Seed on Nutrient Utilization and Serum Biochemical Parameters in Alloxan-Induced Diabetic Rat - Nuria C. Amaechi ,; Philippa C. Ojimelukwe ,; Samuel O. Onoja, (Journal of Pharmacy and Nutrition Sciences, 2018)
The effects of Buchholzia coriacea seed on the nutrient utilization and biochemical parameters in alloxan-induced diabetic rat were evaluated. Buchholzia coriacea (BC) seed was washed, sliced, dried, pulverized and mixed with standard ration at 2.5%, 5%, 10% and 20%. The proximate nutrient composition of the standard and prepared rations was determined. The Buchholzia coriacea incorporated rations and standard ration were fed to alloxan-induced diabetic rats for 70 consecutive days. The nutrient utilization and biochemical parameters as well as the histopathology of pancreas of the treated rats were evaluated. The Buchholzia coriacea at 2.5% inclusion rate significantly (p < 0.05) improved the nutrient utilization and biochemical parameters that were compromised in diabetic rats fed with standard ration alone. The B. coriacea also reversed the pancreatic islet damage induced by alloxan. Buchholzia coriacea have potent antidiabetic and hypolipidemic activities and should not be incorporation in excess of 5% in the diet.